Wind loads and structural response: Benchmarking LES on a low-rise building. (1st August 2017) - Ricci, M.; Patruno, L.; de Miranda, S.
Highlights: Wind loads on a low-rise building are evaluated by means of LES. The incoming flow turbulence is synthetically generated by means of the MDSRFG method. LES results are compared in terms of pressures to experiments for three angles of attack. A comparison between experimental and numerical results in terms of design forces is provided. Abstract: The correct and safe design of structures subjected to the wind actions requires a realistic estimate of the wind effects on their resisting systems. In this context, the present paper proposes a complete numerical study that, starting from Large Eddy Simulation of the turbulent flow around a low-rise building, arrives to the assessment of the wind loading effects, that is the evaluation of design forces in all structural elements. Since it is well known that a realistic representation of the turbulent features found in the lower part of the atmospheric boundary layer is required in order to obtain accurate predictions of the structural response, firstly, the incoming flow turbulence is synthetically generated by means of the Modified Discretizing and Synthesizing Random Flow Generator technique. Then, the obtained synthetic fluctuation field is used as inflow condition for the subsequent Large Eddy Simulations taking into consideration different angles of attack. Results in terms of pressure distributions statistics are analyzed and systematically compared to experimental data. Finally, starting from both simulated and experimental pressure fields, dynamic structural analyses are performed and results directly compared in terms of design forces in the structural elements.